Defining the Meaning of Age - Golab (Iran University of Medical Sciences, 1988)
Extract   If you are young, old or in midlife your new ages activities have different meaning to past times.   Same as the other societies in our society, age is one of the essential dimensions of organizations and social associations. For example our school system is based on the students' ages. Student behavior is different of their adult teachers based on the ages. More or less families, social relationships, social structures and organizations are organized based on the ages.   The age has a basic and important role to play in human relationships and daily experiences. Once a young man sits in the plain and watches to his outfit first question would be how old he/she is, to accommodate his behavior, relations and conversations based on this age.